Biotechnological Applications of Eggshell: Recent Advances - Ahmed, Tamer A. E.; Wu, Ling; Younes, Manar; Hincke, Maxwell (Frontiers in Bioengineering and Biotechnology, 2021)
The eggshell (ES) provides protection against pathogenic and physical insults while supplying essential metabolic and nutritional needs for the growing avian embryo. It is constituted mainly of calcium carbonate arranged as calcite crystals. The global chicken egg production in 2018 was over 76.7 million metric tons. In industrialized countries, about 30% of eggs are processed at breaker plants that produce liquid egg products and large quantities of solid ES waste. ES waste is utilized for a variety of low-value applications, or alternatively is disposed in landfill with associated economic and environmental burdens. The number of patents pertaining to ES applications has increased dramatically in recent years; of 673 patents granted in the last century, 536 (80%) were published in the last two decades. This review provides a snapshot of the most recent patents published between 2015 and 2020, with emphasis on different biotechnological applications of ES waste, and summarizes applications for biomedical, chemical, engineering, and environmental technologies. Biomedical technologies include the production of calcium lactate, calcium phosphate, and health-promoting products, while chemical technologies include plant growth promoters, food processing and production, and biodiesel oil catalysis along with active calcium, carbon, soluble proteins, organic calcium, and ultrafine calcium carbonate sources. Engineering technologies address material engineering and nanoparticle production, while environmental technologies pertain to production of biomass, solubilization of sludge as well as production of magnetic ES adsorbents and adsorption of heavy metals, organic, total nitrogen and fluoride, soil pollutants, and radioactive compounds. Although the number of ES-based patents has exponentially increased in the last decade, exploration of innovative top-down approaches and ES development as a physical platform are new endeavors that are expected to further increase the upscaling of ES waste exploitation.